Primary Carer’s Experiences on the Emerging Sexuality of Adolescents with Intellectual and Developmental Disabilities: A Qualitative Meta-synthesis - Rosna Vincent; R. Nalini; Athira V.H. (Journal of Psychosexual Health)
This study explores primary carer’s experiences concerning the emerging sexuality of adolescents with intellectual and developmental disabilities (IDD) in different cultural and social contexts. Potential studies were collected from four databases: PubMed, Scopus, Science Direct, and Web of Science. Eighteen studies were met the inclusion criteria and published in the year between 2010 and 2022. Four themes were synthesized: Parental perceptions of sexuality, experience of confusion and dilemma, individual needs and uniqueness of the child, and primary carer’s needs. This study highlighted the need for equipping primary caregivers with knowledge and skills to manage and educate the child about sexuality and sexual health.